2021
DOI: 10.2147/nss.s313258
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mediating Role of Anxiety and Depression on the Relationship Between Perceived Stress and Sleep Quality Among Health Care Workers in the COVID-19 Response

Abstract: There is an increasing amount of evidence exploring the adverse effects of perceived stress or anxiety and depression independently on sleep quality during the COVID-19 outbreak, although the underlying mechanisms are unclear. The aim of the current study was to explore the role of anxiety and depression as a potential mediator between perceived stress and sleep quality among health care workers. Methods: Data were collected through an online survey using the snowball sampling method and comprised 588 current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 55 publications
(64 reference statements)
8
22
2
Order By: Relevance
“…Perceived stress is significantly related to depression ( Du et al, 2020 ; Luo et al, 2021 ), which has been proved again in the current study ( Hypothesis 1 ). Moreover, insomnia can be used to explain part of the effect of perceived stress on depression ( Hypothesis 2 ).…”
Section: Discussionsupporting
confidence: 82%
“…Perceived stress is significantly related to depression ( Du et al, 2020 ; Luo et al, 2021 ), which has been proved again in the current study ( Hypothesis 1 ). Moreover, insomnia can be used to explain part of the effect of perceived stress on depression ( Hypothesis 2 ).…”
Section: Discussionsupporting
confidence: 82%
“…However, the relationship between insomnia and depression or anxiety may be bidirectional ( 52 ). Many studies point out that depression or anxiety can reduce the quality of sleep, leading to insomnia ( 17 , 55 , 56 ). Serotonergic and dopaminergic dysfunctions may be the common underlying mechanism of insomnia and mental disorders ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians may also be worried about becoming infected or infecting their families ( 14 ). Stress from these various sources will increase the risk for depression or anxiety if it cannot be effectively allayed ( 15 , 17 ). Moreover, previous studies have shown that compared with older clinicians, young clinicians' lack of practical experience and confidence in clinical management may lead to insufficient resilience to deal with psychological problems and more serious emotional exhaustion ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep; It can be expressed as quality sleep when it is sufficient, quality and regular. In addition, good sleep is vital for health and is one of the most important signs of the transition between health and illness ( Luo et al, 2021 ). The change in sleep quality also directly affects the daily life activities of the individual.…”
Section: Introductionmentioning
confidence: 99%